A Study On Knowledge And Practice Of Covid-19 Biomedical Waste Management Among The Health Care Workers Of Health Facilities Of Rural Ghaziabad. (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Improper waste management has a negative impact on the health of medical professionals, sanitary staff, general public and the environment in general.Objectives: To assess the Knowledge and Practice regarding COVID-19 biomedical waste management (BMWM) among healthcare workers (HCW) of government health facilities of rural Ghaziabad.Methodology: A cross-sectional study was conducted to assess the knowledge and practices regarding Bio-Medical waste, in rural blocks of the district Ghaziabad at C.H.C, P.H.C and Sub-centres. Health care worker (HCW) like Doctor, Nursing Staff, Laboratory technician and Sanitary staff working in the Health care facilities were selected for the Study. A total number of 122 HCW were selected, which included 27 Doctors, 75 Nurse, 06 Lab technician and 14 sanitary staff, using Proportional allocation scheme respectively.Result: The Knowledge regarding Biomedical waste management of COVID-19 was 62.2% and practice was 50.8% among the HCW. Multinomial regression between socio-demographic features of HCW and their practice regarding COVID-19 Biomedical waste revealed that the practice was three times better 3.859 (1.378-10.811) in graduate and four times 4.062 (1.030-16.024) in post graduate than diploma holders. Doctors had three time better 3.595 (1.304-9.908) practice of COVID-19 biomedical waste management than nurses. Similarly, the CHC’s COVID 19 biomedical waste management practices were more than four time 4.440 (1.482-13.974) better than sub centers.Conclusion: Level of knowledge and practice scores were unsatisfactory. Healthcare facilities should provide periodic training and adequate supplies for the waste handlers.